A mass spectrometry and 1H NMR study of hypoglycemic and antioxidant principles from a Castanea sativa tannin employed in oenology. (1st December 2018) - Cardullo, Nunzio; Muccilli, Vera; Saletti, Rosaria; Giovando, Samuele; Tringali, Corrado
Highlights: The ethanol extract of chestnut wood tannin was fractionated on XAD-16. Fraction X3 showed noticeable antioxidant and α-glucosidase inhibitory activities. X3 was fractionized on Sephadex LH20 to give S1-S7. S4-S6 were highly antioxidant fractions, S7 had the highest hypoglycaemic activity. Ellagi- and gallotannins were identified by means of HPLC/ESI-MS/MS and 1 H NMR. Abstract: The ethanol extract of the commercial tannin Tan'Activ C, (from Castanea sativa wood), employed in oenology, was subjected to chromatography on XAD-16 affording fractions X1–X5, evaluated for total phenols content (GAE), antioxidant activity (DPPH, ORAC), and hypoglycemic activity (α-glucosidase inhibition). Fraction X3 showed GAE, radical scavenging activity, and α-glucosidase inhibition higher than those of the Castanea sativa extract, and was subjected to chromatography on Sephadex LH-20 to obtain fractions S1–S7, analyzed by HPLC/ESI-MS/MS and 1 H NMR to identify the main active constituents. In fractions with higher antioxidant activity, gallic acid (4 ), grandinin (5 ), valoneic acid dilactone (9 ), 1, 2, 3-tri- O -galloyl-β-glucose (14 ), 3, 4, 6-tri- O -galloyl-β-glucose (15 ) and galloyl derivative of valoneic acid dilactone (21 ) were identified as the major constituents. The highest hypoglycemic activity was found in fractions S6 and especially S7; the major constituents of these fractions are valoneic acid dilactone (9 ), three tetragalloyl glucose isomers (16 –18 ) and 1, 2, 3, 4, 6-penta- O -galloyl-β-glucose (23 ), previously reported as α-glucosidase inhibitors.